Loss of Ice Cover, Shifting Phenology, and More Extreme Events in Northern Hemisphere Lakes. Issue 10 (11th October 2021) - Sharma, Sapna; Richardson, David C.; Woolway, R. Iestyn; Imrit, M. Arshad; Bouffard, Damien; Blagrave, Kevin; Daly, Julia; Filazzola, Alessandro; Granin, Nikolay; Korhonen, Johanna; Magnuson, John; Marszelewski, Włodzimierz; et al.
Abstract: Long‐term lake ice phenological records from around the Northern Hemisphere provide unique sensitive indicators of climatic variations, even prior to the existence of physical meteorological measurement stations. Here, we updated ice phenology records for 60 lakes with time‐series ranging from 107–204 years to provide the first re‐assessment of Northern Hemispheric ice trends since 2004 by adding 15 additional years of ice phenology records and 40 lakes to our study. We found that, on average, ice‐on was 11.0 days later, ice‐off was 6.8 days earlier, and ice duration was 17.0 days shorter per century over the entire record for each lake. Trends in ice‐on and ice duration were six times faster in the last 25‐year period (1992–2016) than previous quarter centuries. More extreme events in recent decades, including late ice‐on, early ice‐off, shorter periods of ice cover, or no ice cover at all, contribute to the increasing rate of lake ice loss. Reductions in greenhouse gas emissions could limit increases in air temperature and abate losses in lake ice cover that would subsequently limit ecological, cultural, and socioeconomic consequences, such as increased evaporation rates, warmer water temperatures, degraded water quality, and the formation of toxic algal blooms. Plain Language Summary: The timing of lake ice‐on and ice‐off has been observed for decades to centuries because of its importance to refrigeration, transportation, recreation, and cultural traditions. Further, the timing of lake ice is a sensitive indicator of climate as freshwater freezes at 0°C. In our study, we found that ice duration was more than two weeks shorter per century in 60 lakes distributed across the Northern Hemisphere. In the last 25‐year period, trends in ice‐on and duration were over six times faster than in previous quarter centuries. More extremely late ice‐on and early ice‐off years, in addition to years in which a lake did not freeze at all, contributed to this alarming rate of lake ice loss. Mitigation of greenhouse gas emissions is necessary to preserve the existence of annual lake ice cover within this century. Key Points: Lake ice‐on was 11 days later, ice‐off was 7 days earlier, and ice duration was 17 days shorter per century for each lake Trends in ice‐on and ice duration were six times faster in the last 25‐year period (1992–2016) than previous quarter centuries Increased frequency of extreme events, including ice‐free years and short ice durations, were found in larger lakes and warmer regions